Comparison between minimally invasive percutaneous pedicle screw fixation versus open pedicle screw fixation for geriatric osteoporotic spine fracture in a rural hospital - Sajag Gupta (Romanian Neurosurgery)
Background: Research aimed to see if minimally invasive percutaneous pedicle screw fixation (MIPPS)or open pedicle screw fixation (OPS) worked effectively for geriatric osteoporotic fractures (#) of the spine.